The Treatment of Bleeding in Acquired Haemophilia with Recombinant Factor VIIa: A Multicentre Study - Hay, C R M; Negrier, C; Ludlam, C A (Thrombosis and Haemostasis, 1997)
Recombinant factor Vila was used to treat 38 patients with acquired haemophilia participating in the Novoseven compassionate-use program. 19 were male, median age 59, range 2-89 years. The median pre-treatment anti-human (H) and anti-porcine (P) inhibitor titre was H 43 BU/ml (range 1-4500) and P 4.5 BU/ml (range 0-1600). Recombinant factor VIIa was used as first-line therapy for 14 bleeding episodes and as salvage-therapy for 60 episodes which failed to respond to blood-product therapy given for a median of four days (range 1-21 days) prior to treatment with rVIIa. Pre-rVIIa treatment was not reported for four episodes. The indications for treatment were 7 haemarthroses, 40 muscle haematomas, 20 urinary or GI haemorrhages and 3 surgical interventions. The median starting dose of rVIIa was 90.4 ug/kg (range 45-181). A median of 28 doses (range 1-541) were given per episode, over a median 3.9 days (range 0-43).Efficacy was assessed clinically 8 and 24 h after the start of rVIIa and at the end of treatment. A good response was obtained in all 14 bleeds for which rVIIa was used as first-line therapy. The response after 24 h of rVIIa salvage-therapy for 60 bleeds was good in 75%, partial in 17% and poor in 8%. Efficacy was unreported in 4 cases. The median prothrombin time (PTT) shortened from 12 s (range 9.3-20) pre-treatment to 8.8 s (range 6-14) during treatment. The clinical response did not correlate with the dose of rVIIa used, the type of bleed or the degree of shortening of the PTT following rVIIa infusion.Three patients died from haemorrhagic complications of acquired haemophilia. This mortality of 7.9% is lower than previously reported for this condition. Although one patient developed DIC during treatment with rVIIa, this was probably attributable to hypovolaemic shock, massive transfusion and the use of PCCs. This study demonstrates that rVIIa is a safe, useful and effective treatment for bleeding in patients with acquired haemophilia.